Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins. - Postmus, Iris; Trompet, Stella; Deshmukh, Harshal A; Barnes, Michael R; Li, Xiaohui; Warren, Helen R; Chasman, Daniel I; Zhou, Kaixin; Arsenault, Benoit J; Donnelly, Louise A; Wiggins, Kerri L; Avery, Christy L; et al. (Nat Commun, 2014)
Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previously identified in GWAS. Moreover, we confirm the previously described associations with APOE and LPA. Our findings advance the understanding of the pharmacogenetic architecture of statin response.
Keywords: Cholesterol, LDL; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide

Drug-Gene Interactions of Antihypertensive Medications and Risk of Incident Cardiovascular Disease: A Pharmacogenomics Study from the CHARGE Consortium. - Bis, Joshua C; Sitlani, Colleen; Irvin, Ryan; Avery, Christy L; Smith, Albert Vernon; Sun, Fangui; Evans, Daniel S; Musani, Solomon K; Li, Xiaohui; Trompet, Stella; Krijthe, Bouwe P; Harris, Tamara B; et al. (PLoS One, 2015)
BACKGROUND: Hypertension is a major risk factor for a spectrum of cardiovascular diseases (CVD), including myocardial infarction, sudden death, and stroke. In the US, over 65 million people have high blood pressure and a large proportion of these individuals are prescribed antihypertensive medications. Although large long-term clinical trials conducted in the last several decades have identified a number of effective antihypertensive treatments that reduce the risk of future clinical complications, responses to therapy and protection from cardiovascular events vary among individuals. METHODS: Using a genome-wide association study among 21,267 participants with pharmaceutically treated hypertension, we explored the hypothesis that genetic variants might influence or modify the effectiveness of common antihypertensive therapies on the risk of major cardiovascular outcomes. The classes of drug treatments included angiotensin-converting enzyme inhibitors, beta-blockers, calcium channel blockers, and diuretics. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, each study performed array-based genome-wide genotyping, imputed to HapMap Phase II reference panels, and used additive genetic models in proportional hazards or logistic regression models to evaluate drug-gene interactions for each of four therapeutic drug classes. We used meta-analysis to combine study-specific interaction estimates for approximately 2 million single nucleotide polymorphisms (SNPs) in a discovery analysis among 15,375 European Ancestry participants (3,527 CVD cases) with targeted follow-up in a case-only study of 1,751 European Ancestry GenHAT participants as well as among 4,141 African-Americans (1,267 CVD cases). RESULTS: Although drug-SNP interactions were biologically plausible, exposures and outcomes were well measured, and power was sufficient to detect modest interactions, we did not identify any statistically significant interactions from the four antihypertensive therapy meta-analyses (Pinteraction > 5.0×10-8). Similarly, findings were null for meta-analyses restricted to 66 SNPs with significant main effects on coronary artery disease or blood pressure from large published genome-wide association studies (Pinteraction ≥ 0.01). Our results suggest that there are no major pharmacogenetic influences of common SNPs on the relationship between blood pressure medications and the risk of incident CVD.
Keywords: African Americans; Aged; Antihypertensive Agents; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Treatment Outcome

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People